Emotional Resilience and Employee Performance of Commercial Banks in South-East Nigeria - Onyekwelu Njideka Phina; Okeke Anene Patrick; Chikelue Nwabuike (Annals of Human Resource Management Research, 2022)
Purpose: This study examined emotional resilience and performance in commercial banks in South-East Nigeria as the broad objective and specifically examined the extent employee emotional literacy influence performance in commercial banks in South-East Nigeria. Research Methodology: A survey research design was chosen for the study. The population of the study consisted of 250 staff of 5 selected commercial banks in the studied area. The sample size used, as arrived by the use of Krejcie and Morgan sample size formula was 152. The instrument used for data collection was a Likert-structured questionnaire, which was subjected to both validity and reliability test. The data collected were analyzed through the use of a simple regression technique, and the hypothesis was tested at a 5% level of significance. Result: The result revealed that the correlation coefficient as represented by R is .915, signifying a 92% relationship between the variables while R-Square which represented the coefficient of the determination indicates that an 84% change in the performance of employees is accounted for by changes in employee emotional literacy. Limitation: The inferral powers of this study may be questioned as only a region in Nigeria was examined. Contribution: All the studies looked at empirically did not take cognizance of employee emotional literacy as a measure of employee resilience and none of the studies was carried out in southeast, Nigeria, hence, making this work fill an important gap that served as a contribution. Novelty: This study recognized that emotional literacy could be used to measure employee resilience and thus, represents something new within the context of the research area.